PERLINDUNGAN HUKUM TERHADAP IKAN HIU DAN IKAN PARI UNTUK MENJAGA KESEIMBANGAN EKOSISTEM LAUT INDONESIA - Zaka Firma Aditya; Sholahuddin Al-Fatih (Faculty of Law, University of Muhammadiyah Malang, 2016)
The population of sharks and rays in Indonesia threatened with extinction. Based on the findings of WWF Indonesia that there are at least 10 million sharks caught in Indonesian waters each year for commercial purposes. Urgency of protection against sharks and stingrays are not only conservation activities related to efforts to save species of marine animals from extinction, but also related to global environmental issues. Until this time there has been no regulation of the Indonesian government, which specifically provides protection to the conservation of sharks and rays in Indonesia’s marine waters. In this paper, the author will discuss two findings. First, the lack of regulations that provide legal protection to sharks and stingrays from illegal fishing activity. Secondly, there are two efforts can be made by the government, repressive and preventive measures. A repressive measure carried out by law enforcement with a very heavy sanction the perpetrators of fishing of sharks and stingrays. Preventive efforts done by making shark conservation areas and through education and awareness to the community.